Characterization of Soybean Extract Drinks Using Ambon Banana Peel Waste as a Source of Calcium - Miftahul Rizqiah; Muhammad Fajri Romadhan (Food ScienTech Journal, 2024)
Potassium is an important mineral that has many roles in the body. Potassium can be found in fruits and nuts such as ambon banana and soybeans. Ambon banana peel is part of the ambon banana which has not been widely used as processed food or drink. This study aims to determine the best quality ambon banana peel soybean extract based on physical, chemical, and organoleptic characteristics. This research used an experimental method with a completely randomized design (CRD) with one factor with three replications consisting of 6 concentration levels of ambon banana peel extract (P1=10%, P2=15%, P3=20%, P4=25%, P5 = 30%, P6=35). The results showed that the concentration of ambon banana peel was significantly different (α=0.05) on viscosity, stability, total dissolved solids, pH, protein content, fat content, color and taste hedonic tests, hedonic quality tests for color, and taste. However, it was not significantly different in the hedonic aroma and texture test. The best treatment chosen in this study was the P2 treatment (15%) with a viscosity value of 5.52 cps, a stability value of 94.42%, a pH value of 6.71, a total dissolved solids value of 11.07 oBrix, a potassium content of 31.01 mg/100mL, a fat content of 1.42%, a protein content 2.35%, and the overall hedonic value is like the quality attributes of brownish white color, odorless, watery texture, and sweet taste.